2010
DOI: 10.5194/aab-53-689-2010
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of (co)variance function for growth to yearling in Horro sheep of Ethiopia using random regression model

Abstract: Abstract. Random regression analyses of weight data from birth to 396 days were done using 22 141 weight records of 1 951 Horro lambs. Six different models formed from three different orthogonal polynomial regressions (legendre scale)orders (quadratic, cubic, quartic) of fit for both additive genetic and animals’ permanent environmental effects, with assumption of either homogeneous or heterogeneous residual variance, were compared. Fixed effects of year and type of birth, sex and age of dam were fitted along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…Competition for milk consumption among twins and triplets leads to a significant effect of birth type of lambs on the studied traits. Significant influences of investigated fixed effects on body weight of different sheep breed have been confirmed by others (Ghafouri-Kesbi et al 2008, Abegaz et al 2010.…”
Section: Fixed Effectssupporting
confidence: 56%
See 1 more Smart Citation
“…Competition for milk consumption among twins and triplets leads to a significant effect of birth type of lambs on the studied traits. Significant influences of investigated fixed effects on body weight of different sheep breed have been confirmed by others (Ghafouri-Kesbi et al 2008, Abegaz et al 2010.…”
Section: Fixed Effectssupporting
confidence: 56%
“…Such appropriate selective procedure requires accurate (co)variance components and genetic parameter estimates. Genetic parameters for growth traits of different sheep breeds have been reported (Prince et al 2010, Di et al 2011, Abegaz et al 2010. The results of these studies have shown that the inclusion of maternal effects on the models considered for genetic analysis of growth traits, especially for pre-weaning traits, is of crucial importance.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the criteria of values decreased when the order of fit increased in the models, agreeing with the results presented by MOHAMMADI et al (2014a, b); LOPEZ-ROMERO and CARABANO 2003; BIGNARDI et al (2009); EL FARO et al (2008) and ALBUQUERQUE and MEYER (2005); BOHLOULI et al (2013). Therefore, the results showed a significant improvement in the level of fit when the heterogeneous residual variance was included in the model, in comparison to homogeneous residual variance (ABEGAZ et al, 2010;BOHLOULI et al, 2013) and model fit improved with increasing polynomial regression order.…”
Section: The Values Of Comparison Criteriasupporting
confidence: 90%
“…logistic, exponential, Gompertz or Richards models) to the data and estimating genetic parameters for growth curves (LAMBE et al, 2006) or using random regression model (RRM) (LEWIS and BROTHERSTONE, 2002;FISCHER et al, 2004;MOLINA et al, 2007). Currently RRM is being applied for genetic evaluation in growth trait such cattle (KREJCOVA et al, 2007;NESER et al, 2012;BOHLOULI et al, 2013), sheep (LEWIS and BROTHERSTON, 2002;GHAFOURI KESBI et al, 2008;ABEGAZ et al, 2010;KARIUKI et al, 2010;WOLC et al, 2011 ) and pig (HUISMAN et al, 2002) data. These models use polynomials in time to describe mean profiles with random coefficients to generate a correlation among the repeated observations on each individual (ROBERT GRANIE et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The order of fit for the random effects was kept constant to define the best variance structure to model the residual variances. The results of log L, AIC, BIC and LRT indicated a significant improvement in the level of fit when the heterogeneous residual variance was included in the model, in comparison to homogeneous residual variance (ABEGAZ et al, 2010) and model fit improved with increasing polynomial regression order to 3.3.het3 model and then worsened to 6.6.het3 model. These indicated that residual variances had different behavior along the age.…”
Section: Discussion Log Likelihoods and Information Criteriamentioning
confidence: 96%